ANALYZING THE INFLUENCE OF BRAND IMAGE, PERCEIVED PRICE AND PERCEIVED QUALITY ON CONSUMER BUYING DECISION OF LOW COST GREEN CAR (CASE STUDY OF: ASTRA TOYOTA AGYA AT MANADO) - Lalujan, David I. O. (Sam Ratulangi University, 2016)
The Ministry of Industry issued a regulation No.33/M-IND/PER/7/2013 about production development of LCGC On September 2013, and itâ€™s has experienced impressive growth in Indonesia automotive sector since 2013. LCGC is an abbreviation of Low Cost Green Car. Literally means 'cheap car environmental friendly' in Indonesian â€mobil murah ramah lingkunganâ€. The main purpose of this research is to analyze what drive people to buying LCGC Astra Toyota Agya and measured by three dependent variables (brand image, perceived price and perceived quality) .This study is going to use multiple linear regression analysis to analyze the consumer buying decision to buy the LCGC Astra Toyota Agya. The numbers of respondents are 53 consumers. The 53 consumers are taken from PT. Hasjrat Abadi Toyota Tendean, those consumers are already bought the LCGC Astra Toyota Agya in 2016 from month January-April. The result of this study shows that brand image, perceived price and perceived quality simultaneous have significant effects on consumer buying decision, brand image partial does not significant effect on consumer buying decision, perceived price and perceived quality partially has significant effect on consumer buying decision of LCGC Astra Toyota Agya in Manado. LCGC Astra Toyota Agya should improve their advertisement of Agya and quality even the quality of the car is the best on its class; such as adding side-beam impact for safety and a new extraordinary color. So it will increase buying interest and strengthen competitiveness of fellow LCGC products.